2019
DOI: 10.1146/annurev-pharmtox-010818-021818
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Immunopharmacogenomics: Predicting, Preventing, and Understanding Immune-Mediated Adverse Drug Reactions

Abstract: Adverse drug reactions (ADRs) are a significant health care burden. Immune-mediated adverse drug reactions (IM-ADRs) are responsible for one-fifth of ADRs but contribute a disproportionately high amount of that burden due to their severity. Variation in human leukocyte antigen (HLA) genes has emerged as a potential preprescription screening strategy for the prevention of previously unpredictable IM-ADRs. Immunopharmacogenomics combines the disciplines of immunogenomics and pharmacogenomics and focuses on the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 155 publications
0
34
0
Order By: Relevance
“…Furthermore, multiple case studies have observed that CYP2C9 PMs are at increased risk for exposure‐related phenytoin toxicities, and multiple studies have observed an association between the CYP2C9*3 allele and SJS/TEN 25–27 . Although carriage of the CYP2C9*3 allele is insufficient to predict phenytoin‐induced SJS/TEN, these and other data suggest that the risk of SJS/TEN is dose‐related and provide an additional rationale for reducing phenytoin dose in CYP2C9 PMs 28 . Thus, our recommendations are conservative given the variability surrounding phenytoin dosing.…”
Section: Drugs: Phenytoin and Fosphenytoinmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, multiple case studies have observed that CYP2C9 PMs are at increased risk for exposure‐related phenytoin toxicities, and multiple studies have observed an association between the CYP2C9*3 allele and SJS/TEN 25–27 . Although carriage of the CYP2C9*3 allele is insufficient to predict phenytoin‐induced SJS/TEN, these and other data suggest that the risk of SJS/TEN is dose‐related and provide an additional rationale for reducing phenytoin dose in CYP2C9 PMs 28 . Thus, our recommendations are conservative given the variability surrounding phenytoin dosing.…”
Section: Drugs: Phenytoin and Fosphenytoinmentioning
confidence: 93%
“…[25][26][27] Although carriage of the CYP2C9*3 allele is insufficient to predict phenytoin-induced SJS/TEN, these and other data suggest that the risk of SJS/TEN is dose-related and provide an additional rationale for reducing phenytoin dose in CYP2C9 PMs. 28 Thus, our recommendations are conservative given the variability surrounding phenytoin dosing. Based on the doses reported in the pharmacokinetic and pharmacogenetic studies mentioned above [29][30][31] and in Table S2, a typical initial or loading dose followed by at least a 25% reduction in the recommended starting maintenance dose may be considered for CYP2C9 IMs with AS of 1.0.…”
Section: Reviewmentioning
confidence: 99%
“…Genetic predisposition, particularly HLA risk, is important for several delayed IM-ADRs and has been reviewed recently for a number of drugs relevant to HIV, including the antiretrovirals abacavir, nevirapine and certain antiinfectives, for example, dapsone [37]. These genetic risk factors are critical determinants of certain IM-ADRs prior to HIV infection.…”
Section: Mechanisms Of Drug Hypersensitivitymentioning
confidence: 99%
“…(vi) Co-signaling pathways also regulate T-cell activation, with overall co-inhibition or co-stimulation leading to (vii) cytokine release and respective tolerance with T-regulatory cell (Treg)-induced immunosuppression or inflammation and cytotoxic degranulation, respectively. expressed in <1% of patients of European or African ancestry despite global disease burden, restricting universal screening and inferring that different HLA alleles drive reactions in different populations (Karnes et al, 2019). Indeed, multiple alleles are now associated with CBZ-SCAR in distinct populations, with HLA-A * 31:01 associated with DRESS in Europeans and Chinese, but not SJS/TEN (McCormack et al, 2011;Genin et al, 2014), highlighting propensity for distinct alleles to define risk for specific reactions.…”
Section: Carbamazepine Hypersensitivitymentioning
confidence: 99%